2013
DOI: 10.14260/jemds/885
|View full text |Cite
|
Sign up to set email alerts
|

Pterion Its Location and Clinical Implications- A Study Compared

Abstract: Pterion a cranio-metric point has been described according to its location, type and relationship with the surrounding bony landmarks. Approach through pterion is mostly used to treat lesions of anterior and middle cranial fossa. Pterion ossicle or Epipteric bone are sometimes mistaken as a fracture at this point. AIM & OBJECTIVE: The study was set to explore the morphometry of Pterion in the human dry skulls of Uttarakhand region. The data may be useful for the anthropologists, forensic pathologists, neurosur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…Lee et al reported the incidence of epipteric type of pterion as 40.5% which is very high compared to present study [14]. Ethnic variation was observed in the location of pterion as the average distance from the center of pterion to mid-point on zygomatic arch was 37.40±3.92 mm in the present study, which was less than that mentioned by the Ukoha et al, and Eboh et al, in Nigerian skulls but similar to that reported by Suchit et al, and Hari Prasad et al, in north Indian skulls [6,16,17,19]. The average distance between the center of pterion to fronozygomatic suture, anterosuperior margin of external auditory meatus and inferior point on mastoid process of the present study were similar to the results of North Indian studies.…”
Section: Discussionsupporting
confidence: 63%
“…Lee et al reported the incidence of epipteric type of pterion as 40.5% which is very high compared to present study [14]. Ethnic variation was observed in the location of pterion as the average distance from the center of pterion to mid-point on zygomatic arch was 37.40±3.92 mm in the present study, which was less than that mentioned by the Ukoha et al, and Eboh et al, in Nigerian skulls but similar to that reported by Suchit et al, and Hari Prasad et al, in north Indian skulls [6,16,17,19]. The average distance between the center of pterion to fronozygomatic suture, anterosuperior margin of external auditory meatus and inferior point on mastoid process of the present study were similar to the results of North Indian studies.…”
Section: Discussionsupporting
confidence: 63%
“…Results of current study are in line with Mishra et al 1 and K Epharaim Vikram Rao 2 Mwachaka et al [8] Apinhasmit et al [11] Kumar S. et al [13] Whereas mean values of present study are slightly less than those of Oguz et al [7], Ukohla et al [12] and Eboh and Obaroefe [14].…”
Section: Discussionsupporting
confidence: 90%
“…The one with the highest incidence of these is the sphenoparietal type with the rate of 74% to 95.3%. [30][31][32] In classical anatomy notes, the location of the pterion, which is considered to be 1 cm in diameter, is described as approximately 2.6 cm posterior and 1.3 cm superior to the posterolateral margin of the frontozygomatic suture and 4 cm above the mid-point of the zygomatic arch. 26,33 The pterion was named as "high pterion" in case it is located over 40.0 mm.…”
Section: Discussionmentioning
confidence: 99%
“…The one with the highest incidence of these is the sphenoparietal type with the rate of 74% to 95.3%. 30-32…”
Section: Discussionmentioning
confidence: 99%